The Christian Hope - Hebblethwaite, Brian (Oxford ; New York : Oxford University Press, 2010)
What does it mean to hope for heaven? Brian Hebblethwaite traces the background to the Christian hope in the faith of Israel, examines its primary basis in the acts of God in the story of Jesus Christ, and follows the history of Christian attitudes to the future of humanity and of creation throughout the Christian centuries. The Christian Hope tells the complex story of the different strands, emphases and problems that have developed between biblical times and our own in the quest to understand 'the four last things' -death, judgement, heaven and hell.
Part One. The Hope of Israel and the First Christians -- Part Two. The Classical Christian Hope -- Part Three. The Christian Hope in the Modern Age -- Bibliography -- Index of Biblical Passages -- Index of Names and Topics.
Previous ed.: Basingstoke: Marshall Morgan & Scott, 1984.
Includes bibliographical references (p. [227]-233) and indexes.
Keywords: Hope -- Religious aspects -- Christianity; Future life -- Christianity; Christianity; Future life -- Christianity; Hope -- Religious aspects -- Christianity; Hope -- Religious aspects; Religion; RELIGION / Faith; Electronic books